The Fruits of Integration : Black Middle-Class Ideology and Culture, 1960-1990 - Banner-Haley, Charles Pete T., 1948- (Book collections on Project MUSE., 1994)
This history of a pivotal group in American society will cause reflection, discussion, and debate. It shows how the black middle class is both a shaper and a mirror and indeed a key force in the "Africanizing" of American culture. In the past three decades the fruits of integration have been at once sweet and bitter. This study of the era explores both the progress and the setbacks and shows how the achievements of African Americans in entering the nation's mainstream have been propelled by the culture and the ideology of the black middle class. In late twentieth-century America the black middle class has occupied a unique position. It greatly influenced the way African Americans were perceived and presented to the greater society, and it set roles and guidelines for the nation's black masses. Though historically a small group, it has attempted to be a model for inspiration and uplift. In the struggle for equality and the fight against racism pervasive in American society, its own members have wrestled with their own vision of racial identity and solidarity. Here is a concept of "integrative cultural diversity" that affirms the importance of the African-American presence to the nation's culture and advocates cultural diversity as a movement away from racism and towards an America that is a humane and comfortable society for all. In examining the growth of the black middle class and its responses to political and social realities in the decades since 1960, The Fruits of Integration acknowledges the burgeoning of a bitter and despairing underclass and its desperate separatism. Yet this book focuses on the role of the expanded middle class struggling as never before to provide a vision of harmony for all Americans.